The Influence of Financial Ratios on Net Profit Growth in Manufacturing Companies in the Basic and Chemical Industry Sub-Sectors Listed on the Indonesia Stock Exchange - Adella Viona; Maya Syaula; Noni Ardian (International Journal of Management, Economic and Accounting, 2024)
This study aimed to analyze the influence of the current ratio, debt-to-equity ratio, return on assets, total asset turnover, and price-to-book value on net profit growth among manufacturing companies within the basic and chemical sectors listed on the Indonesia Stock Exchange. Data for the research, spanning the years 2017 to 2023, was sourced from www.idx.co.id, and the study was carried out in 2024. From a population of 61 companies, a sample of 38 was selected. Quantitative data analysis was performed using Eviews 9, employing a panel data regression approach. Findings indicated that, individually, only the return on assets had a positive and statistically significant impact on net profit growth, while the current ratio, debt-to-equity ratio, total asset turnover, and price-to-book value showed no significant partial effect on net profit growth. However, collectively, these variables (current ratio, debt-to-equity ratio, return on assets, total asset turnover, and price-to-book value) significantly and positively affected net profit growth in the targeted manufacturing companies. Together, these variables contributed 26.05% to net profit growth, demonstrating a fairly strong correlation with the dependent variable.